2019
DOI: 10.1186/s12891-019-2917-1
|View full text |Cite
|
Sign up to set email alerts
|

Workplace injury and associated factors among construction workers in Gondar town, Northwest Ethiopia

Abstract: BackgroundThe construction industry is one of the most hazardous working areas, where the highest number of labourers engaged. However, the predisposing factors for occupational injury in the construction sites in Ethiopia are not well investigated. This study was, therefore, conducted to assess the magnitude of occupational injury and associated factors among construction workers in Gondar town, northwest Ethiopia.MethodsThis cross-sectional study was conducted on 566 construction workers. Systematic random s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 58 publications
(49 reference statements)
9
30
1
Order By: Relevance
“…Twenty percent of the workers they studied were female [8]. Although construction work is usually considered as male dominated [15], the proportion of female construction workers in the other studies in East Africa ranged from 24-48% [9,11,12]. The current study had a much smaller proportion of women (3.1%).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Twenty percent of the workers they studied were female [8]. Although construction work is usually considered as male dominated [15], the proportion of female construction workers in the other studies in East Africa ranged from 24-48% [9,11,12]. The current study had a much smaller proportion of women (3.1%).…”
Section: Discussionmentioning
confidence: 55%
“…Subjectively, many contractors indicated that they felt investing in PPE was not warranted. There have been several other studies that reported PPE use and other aspects of safety among building construction workers in Africa [8][9][10][11][12]. Alemu et al interviewed 206 building construction workers in Addis Ababa, Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics Of Original Articles In this study to estimate the pooled magnitude of work related injury a total of 8025 workers from MSWM, construction and textile industry were involved. Concerning geographical distribution of the studies, the 17 studies were obtained from the four regions of the country: six studies from Addis Ababa (10,19,(21)(22)(23)30), three from Oromia (24,27,29), seven (7) from Amhara (11,17,18,20,25,26,28), and one from Southern Nations, Nationalities and Peoples' Region (SNNPR) (29). The highest prevalence of occupational injury and illness (84.7%) was reported in Addis Ababa (10) whereas the lowest prevalence (31.4%) was reported from a study done in Arba Minch (SNNPR) (9).…”
Section: Search Resultsmentioning
confidence: 99%
“…Lastly the pooled odds of work related injury among those workers using PPE was 52% less than those who did not use PPE at work place (0.48 (95%CI: 0.36, 0.65)). To calculate the pooled odds ratio of alcohol drinking habit (9,11,17,18,26,28,30,31), cigarette smoking habit (18,24,26,30,31), khat chewing habit (9, 22, 26-28, 30, 31), work related stress (9,20,26,29,30), level of education (9,11,18,24,26,30,31), and use of PPE (9,11,18,19,22,26,27,(29)(30)(31) reports of a minimum of 5 to 10 studies were included.…”
Section: Subgroup Analysismentioning
confidence: 99%